Pengaruh Arang Tempurung Kelapa Sebagai Pengganti Sebagian Pasir Terhadap Kuat Tekan Beton - Riyanto, Priyanbudi Ahmad; Azhari; Ermiyati (Jurnal Vokasi Manajemen Dan Rekayasa Infrastruktur Sipil, 2025)
Aggregate is the main component in making concrete with an amount reaching 70%-75% of the total volume of concrete. Fine aggregate itself generally occupies 25%-65% of the total aggregate volume. The large use of concrete in construction is followed by a large demand for sand. The use of charcoal from coconut shell waste as a partial substitute for sand in concrete has been studied to show an increase in the compressive strength of concrete mixed with coconut shell charcoal in certain doses. This study examines the effect of partial substitution of sand with coconut shell charcoal on the compressive strength of concrete with variations of 6%, 7%, 7.5%, 8%, and 9% of the weight of the sand. In addition, comparative test objects were also made without a mixture of charcoal which was normal concrete. The results of the study showed an increase in the compressive strength of concrete mixed with charcoal in all variations compared to normal concrete. The maximum concrete compressive strength was obtained at 263.7 kg/cm2, an increase of 17.2% compared to normal concrete, occurring at 8% coconut shell charcoal substitution which was the optimum dose for concrete compressive strength in this study.